1999
DOI: 10.1152/jn.1999.81.5.2164
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Bistability in Spinal Motoneurons In Vivo by the Noradrenergic α1 Agonist Methoxamine

Abstract: Enhancement of bistability in spinal motoneurons in vivo by the noradrenergic alpha1 agonist methoxamine. Like many types of motoneurons, spinal motoneurons in the adult mammal can exhibit bistable behavior. This means that short periods of excitatory input can initiate long periods of self-sustained firing and that equally short periods of inhibition can return the cell to the quiescent state. Usually, the presence of one of the monoamines (either serotonin or norepinephrine) is required for spinal motoneuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 37 publications
9
166
2
Order By: Relevance
“…Much of the work to date has focused on monoaminergic regulation of motoneuron properties. Specifically, serotonin and noradrenaline have been studied and shown to modulate PICs (Section 6; see also Lee and Heckman, 1999;Heckman et al, 2003) and voltage threshold (Fedirchuk and Dai, 2004).…”
Section: Other Possible Mechanisms Of Modulation Of Motoneuron Propermentioning
confidence: 99%
“…Much of the work to date has focused on monoaminergic regulation of motoneuron properties. Specifically, serotonin and noradrenaline have been studied and shown to modulate PICs (Section 6; see also Lee and Heckman, 1999;Heckman et al, 2003) and voltage threshold (Fedirchuk and Dai, 2004).…”
Section: Other Possible Mechanisms Of Modulation Of Motoneuron Propermentioning
confidence: 99%
“…Prior to spinal cord injury, PICs are present and prominently amplify normal motoneuron output (Hounsgaard et al 1988;Lee and Heckman 1999); however, low-threshold long EPSPs do not appear to be prominent, and there is strong descending and segmental inhibitory control that can terminate motoneuron firing, even though it is maintained by intrinsic PICs (Fig. 7, long inhibitory reflex).…”
Section: Amplification and Prolongation Of Reflexes With Chronic Injurymentioning
confidence: 99%
“…Acutely, hours or days after the injury, the spinal cord is nonexcitable. This lack of excitability is predictable from a number of studies of the intrinsic electrical properties of motoneurons, which have shown that motoneuron excitability is dependent on inputs descending from the brain stem and releasing the neuromodulators serotonin and norepinephrine, and this is lost after injury (Conway et al 1988;Hounsgaard et al 1988;Lee and Heckman 1999). Such neuromodulators allow the motoneuron to exhibit sustained depolarizations known as plateau potentials, which are due to slowly activating voltage-dependent persistent inward currents (PICs), in large part mediated by the low-voltage-activated Cav1.3 L-type calcium channels in the dendrites (Hounsgaard and Kiehn 1989;Perrier and Hounsgaard 2003;Powers and Binder 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The stable firing rates of motor neurons of PLS patients would be compatible with activation of a plateau potential, albeit at an abnormally low membrane potential. Low-voltage plateau potentials could occur if channels were activated at an extremely low voltage, even below threshold for firing, as could theoretically occur under conditions of high monoaminergic tone (Hounsgaard and Kiehn 1989;Lee and Heckman 1999) or if the numbers of channels were reduced. In animal models of chronic spinal injury, the voltage threshold for persistent inward currents was found to be less than the firing threshold for the motor neuron (Li and Bennett 2003;Li et al 2004).…”
Section: Discussionmentioning
confidence: 99%